2006
DOI: 10.1016/s0022-5347(05)00695-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Serum Marker, Total Prostate Secretory Protein of 94 Amino Acids, Improves Prostate Cancer Detection and Helps Identify High Grade Cancers at Diagnosis

Abstract: Patients with low total PSP94 levels had a high probability for having prostate cancer detected at biopsy. The total PSP94 level was able to help identify patients with high grade disease among a subset of patients in whom PSA and FTPSA are least informative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 18 publications
2
57
1
2
Order By: Relevance
“…Bound forms of PSP94 exist as a complex with PSP94-binding protein. Serum concentrations of the ratio of PSP94 to free PSP94 and serum concentrations of PSP94-binding protein in CaP patients after local surgery were associated with Gleason sum, biochemical recurrence, and surgical margin status (52 ). Large prospective studies are still required to validate this candidate biomarker.…”
Section: Prostate Secretory Protein 94 and Binding Proteinmentioning
confidence: 99%
“…Bound forms of PSP94 exist as a complex with PSP94-binding protein. Serum concentrations of the ratio of PSP94 to free PSP94 and serum concentrations of PSP94-binding protein in CaP patients after local surgery were associated with Gleason sum, biochemical recurrence, and surgical margin status (52 ). Large prospective studies are still required to validate this candidate biomarker.…”
Section: Prostate Secretory Protein 94 and Binding Proteinmentioning
confidence: 99%
“…[13][14][15] Serum levels of MSMB, its binding protein PSP94-binding protein (PSPBP) and the ratio free/bound MSMB, have all been suggested as independent prognostic factors in prostate cancer. [16][17][18][19] We have previously reported that the cysteine-rich secretory family (CRISP) family member CRISP3 also forms a high-affinity complex with MSMB in human seminal plasma. 20 CRISP3 has been found to be one of the most upregulated genes in prostate cancer compared to benign tissue, 21,22 and was proposed to be a useful biomarker for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Two interacting prostate proteins, namely, the prostatic secretory protein of 94 amino acids (PSP94), encoded by the MSMB gene, and the cysteine-rich secretory protein CRISP-3, also known as SGP28, have been advanced as PCa biomarkers. [2][3][4][5] In parallel, much attention has gone to the functional characterization of these proteins. Pathak et al 6 now report in the Asian Journal of Andrology that both PSP94 and CRISP-3 function as growth inhibitors of subsets of PCa cell lines, despite their inversely correlated expression levels during PCa progression ( Figure 1a).…”
mentioning
confidence: 99%